(untitled) (Global Journal of Human-Social Science, 2023)
The present article aims to present the data recorded in the Permanent Education Municipal Plans (Planos Municipais de Educação Permanente -PLAMEP) regarding the educational activities offered to professionals working in Primary Care services under the Regional Health Coordination Office -East in the period from 2017 to 2020. The article seeks to highlight the quantity and type of areas/themes proposed; of actions offered and their periodicity. Some important issues have emerged in this survey, among them: the prevalence of more vertical methods deployed in educational actions, such as training and courses, along with a prevalent monthly periodicity of such activities; differences in the amount of educational actions proposed in the course of the period considered; a diversity of actions not circumscribed to the areas previously defined in the survey; the lack of filling in some information such as executing area and periodicity in the first years of the PLAMEP implementation; the lack of standardization and uniformity in the spreadsheets of 2017 and 2018; and an improvement in the organization of data between 2019 and 2020.